The struggle for self-identity and transformation of the female characters: A critical reading of the Metamorphosis and A Doll’s House - Jahan, Zerin (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2020.